European bio-naïve spondyloarthritis patients initiating TNF inhibitor: time trends in baseline characteristics, treatment retention and response - Christiansen, Sara Nysom; Ørnbjerg, Lykke Midtbøll; Rasmussen, Simon Horskjær; Loft, Anne Gitte; Askling, Johan; Iannone, Florenzo; Zavada, Jakub; Michelsen, Brigitte; Nissen, Michael; Onen, Fatos; Santos, Maria Jose; Pombo-Suarez, Manuel; et al. (Rheumatology (Oxford, England), 2022)
OBJECTIVES: To investigate time trends in baseline characteristics and retention, remission and response rates in bio-naïve axial spondyloarthritis (axSpA) and psoriatic arthritis (PsA) patients initiating TNF inhibitor (TNFi) treatment. METHODS: Prospectively collected data on bio-naïve axSpA and PsA patients from routine care in 15 European countries were pooled. Three cohorts were defined according to year of TNFi initiation: A (1999-2008), B (2009-2014) and C (2015-2018). Retention, remission and response rates were assessed at 6, 12 and 24 months. RESULTS: In total, 27 149 axSpA and 17 446 PsA patients were included. Cohort A patients had longer disease duration compared with B and C. In axSpA, cohort A had the largest proportion of male and HLA-B27 positive patients. In PsA, baseline disease activity was highest in cohort A. Retention rates in axSpA/PsA were highest in cohort A and differed only slightly between B and C. For all cohorts, disease activity decreased markedly from 0 to 6 months. In axSpA, disease activity at 24 months was highest in cohort A, where also remission and response rates were lowest. In PsA, remission rates at 6 and 12 months tended to be lowest in cohort A. Response rates were at all time points comparable across cohorts, and less between-cohort disease activity differences were seen at 24 months. CONCLUSION: Our findings indicate that over the past decades, clinicians have implemented more aggressive treatment strategies in spondyloarthritis. This was illustrated by shorter disease duration at treatment initiation, decreased retention rates and higher remission rates during recent years.
Keywords: Spondylarthritis; psoriatická artritida; Arthritis, Psoriatic; Cohort Studies; výsledek terapie; mužské pohlaví; time trends; axial spondyloarthritis; kohortové studie; psoriatic arthritis; remission; Humans; response; TNFi retention; spondylartritida; inhibitory TNF; Tumor Necrosis Factor Inhibitors; Treatment Outcome; lidé; Male